EFEKTIVITAS PEMBELAJARAN SEJARAH DENGAN MENGUNAKAN MODEL PEMBELAJARAN E â LEARNING - Wibowo, Heros Satrio (Indonesian Journal of History Education, 2014)
Results of preliminary observations about the learning process, SMA 9 Semarang not use a model-based learning or e-learning facilities for procuring models whereas e-learning is very adequate as: hostpot area, LAN, projector, computer and so on. The many advantages of e-learning model of this led the authors are interested in doing this experiment teaching methods at the school. Problems in this study: (1) how the application of learning models Colonialism and Imperialism lecture material in Indonesian West in Class XI Social High School 9 Semarang ?, (2) how the implementation of e-learning materials Colonialism and Imperialism in Indonesian West in Class XI social education High School 9 Semarang ?, (3) How can the effectiveness of learning history by using the model of e-learning materials colonialism and western imperialism in Indonesia in class XI Social High School 9 Semarang.Â Hasil dari observasi awal mengenai proses pembelajaran, SMA Negeri 9 Semarang belum mengunakan model pembelajaran berbasis elektronik atau e-learning padahal fasilitas untuk pengadaan model pembelajaran e-learning sangat memadai seperti: hostpot area, LAN, projector, computer dan sebagainya. Banyaknya keunggulan dari model pembelajaran e-learning ini menyebabkan penulis tertarik untuk melakukan eksperimen metode pembelajaran ini di sekolah tersebut. Permasalahan dalam penelitian ini: (1) bagaimanakah penerapan model pembelajaran ceramah materiÂ  Kolonialisme dan Â Imperialisme Barat di Indonesia pada siswa kelas XI IPS SMA N 9 Semarang?, (2) bagaimanakah penerapan e-learning materiÂ  Kolonialisme dan Imperialisme Barat di Indonesia pada siswa kelas XI IPS SMA N 9 Semarang?, (3) BagaimanaÂ  efektifitas pembelajaran sejarah dengan mengunakan model pembelajaran e-learning materiÂ  Kolonialisme dan Imperialisme Barat di Indonesia pada siswa kelas XI IPS SMA N 9 Semarang. Â Â